DPOAE Intensity Increase at Individual Dominant Frequency after Short-Term Auditory Exposure. (5th September 2013) - Bakk, Judit; Karosi, Tamás; Batta, Tamás József; Sziklai, István
Abstract : Previous experiments suggested the possibility of a short-term sound stimulus-evoked and transient increase in DPOAE amplitudes. This phenomenon is possibly due to the complexity of the outer hair cells and their efferent control system and the different time scales of regulatory processes. A total of 100 healthy subjects ranging from 18 to 40 years of age with normal hearing and normal DPOAE values in the range of 781–4000 Hz were recruited in the study. Diagnostic DPOAE measurements were performed after short-term sound exposure. We proposed a 10 sec, 50 dB sound impulse as the most effective stimulus for clinical practice between 40 and 60 sec poststimulus time to detect the aforementioned transient DPOAE increase. We developed a procedure for detection of this transient increase in DPOAE by the application of a short-term sound exposure. The phenomenon was consistent and well detectable. Based on our findings, a new aspect of cochlear adaptation can be established that might be introduced as a routine clinical diagnostic tool. A mathematical model was provided that summarizes various factors that determine electromotility of OHCs and serves as a possible clinical application using this phenomenon for the prediction of individual noise susceptibility.